The Ancient Allan - Haggard, H. Rider (Henry Rider), 1856-1925 (Salt Lake City, UT : Project Gutenberg, 2004)
"The Ancient Allan" by H. Rider Haggard is a novel featuring the hunter Allan Quatermain. When Quatermain and Lady Ragnall inhale Taduki, a drug inducing visions of past lives, they experience ancient incarnations in Persian-ruled Egypt. Quatermain relives his existence as Egyptian aristocrat Shabaka during a revolt against Persian domination, while familiar characters reappear in different forms. This adventure blends historical romance with fantastical elements of reincarnation, telepathy, and Egyptian mysticism, suggesting the goddess Isis's curse follows characters through successive lifetimes. (This is an automatically generated summary.)
Wikipedia page about this book: https://en.wikipedia.org/wiki/The_Ancient_Allan
Release date is 2004-05-01
John Bickers, Dagny and David Widger
Keywords: Quatermain, Allan (Fictitious character) -- Fiction